Virtue Ethics and Contemporary Aristotelianism : Modernity, Conflict and Politics - Bielskis, Andrius (Bloomsbury Studies in the Aristotelian Tradition Ser, 2020)
Intro -- Title Page -- Copyright Page -- Contents -- Contributors -- Introduction -- Part 1: The Aristotelian tradition of virtues -- Chapter 1: Four - or more? - political Aristotles -- I -- II -- III -- IV -- V -- Bibliography -- Chapter 2: Plato and Aristotle on nature and society -- I -- II -- III -- IV -- V -- VI -- VII -- Notes -- Bibliography -- Chapter 3: 'Managers would not need subordinates and masters would not need slaves' -- Introduction -- Aristotle's account of phusis -- From Physics to the Generation of Animals -- The relationships of oikia and political rule -- The case of slavery: A reconsideration -- Oikonomikē, chrēmatistikē, kapilikē and a concluding remark -- Notes -- Bibliography -- Chapter 4: Aristotle and two senses of happiness -- I What does happiness consist in? -- II Encountering a monist account -- III What kind of life is the happiest life? -- IV Conclusion -- Notes -- Bibliography -- Chapter 5: 'Going through time together': Aristotelian friendship and the criterion of time -- I Philia and suzēn: The criterion of time and the test of friendship -- II The object of love and the forms of Aristotelian friendship -- III 'Living together' as an essential requirement for friendship: Chronos, kairos and philia -- IV Conclusion -- Notes -- Bibiography -- Chapter 6: Byzantine Thomism: Aristotelianism and Thomas Aquinas' reception in Byzantium -- Introduction -- I Philosophical and theological controversies in late Byzantium -- II Contacts between Byzantines and Latins in the fourteenth century -- III Demetrius Cydones' encounter with Thomas Aquinas -- IV The edition princeps of the Secunda Secundae -- Notes -- Bibliography -- Part 2: Modernity, conflict and MacIntyrean Aristotelianism -- Chapter 7: Aristotelianism, Austinianism and the problem of the good -- Notes -- Bibliography.